2018
DOI: 10.1038/s41467-017-02440-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical Wnt signaling regulates neural stem cell quiescence during homeostasis and after demyelination

Abstract: Adult neural stem cells (NSCs) reside in a specialized microenvironment, the subventricular zone (SVZ), which provides them with unique signaling cues to control their basic properties and prevent their exhaustion. While the signaling mechanisms that regulate NSC lineage progression are well characterized, the molecular mechanisms that trigger the activation of quiescent NSCs during homeostasis and tissue repair are still unclear. Here, we uncovered that the NSC quiescent state is maintained by Rho-GTPase Cdc4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 70 publications
5
60
0
Order By: Relevance
“…NSC adhesion to the apical niche is maintained through the ncWnt signaling, which in turn regulates Notch signaling activity. Strikingly, as a result of a demyelination injury, tissue homeostasis and repair depends on the downregulation of the ncWnt/Cdc42 axis and activation of canonical Wnt (cWnt)/β-catenin signaling in SVZ NSCs (Chavali et al, 2018 ).…”
Section: Factors Regulating Normal Cell Quiescencementioning
confidence: 99%
“…NSC adhesion to the apical niche is maintained through the ncWnt signaling, which in turn regulates Notch signaling activity. Strikingly, as a result of a demyelination injury, tissue homeostasis and repair depends on the downregulation of the ncWnt/Cdc42 axis and activation of canonical Wnt (cWnt)/β-catenin signaling in SVZ NSCs (Chavali et al, 2018 ).…”
Section: Factors Regulating Normal Cell Quiescencementioning
confidence: 99%
“…15,16 However, recent findings have revealed that Ror1 and/or Ror2 are expressed in the tissue stem cells not only during the embryonic development but also in adulthood. [17][18][19][20][21][22] In the adult skeletal muscles, Ror1 is expressed selectively in the adult muscle stem cells, known as satellite cells (SCs), and its expression in SCs can be further enhanced after muscle injury, leading to increased proliferation of SCs, thereby promoting regeneration of the damaged skeletal muscles. 20 In addition, expression of Ror2 is increased in reactive astrocytes that acquire stem cell-like properties in the injured brains, leading to increased proliferation of reactive astrocytes, thereby promoting repair following brain injury.…”
mentioning
confidence: 99%
“…Wnt signaling has a canonical and a non-canonical branch depending on the downstream involvement of the β-catenin pathway [52]. A shift from the non-canonical to canonical Wnt pathway has been associated with the activation of quiescent NSCs in the lysolecithin model of focal demyelination [53], and β-Catenin signaling is active during remyelination [54]. Indeed, canonical β-catenin dependent [55] and noncanonical β-catenin independent [53] Wnt signaling has been attributed a crucial role in remyelination, although this issue remains controversial [55].…”
Section: Discussionmentioning
confidence: 99%
“…A shift from the non-canonical to canonical Wnt pathway has been associated with the activation of quiescent NSCs in the lysolecithin model of focal demyelination [53], and β-Catenin signaling is active during remyelination [54]. Indeed, canonical β-catenin dependent [55] and noncanonical β-catenin independent [53] Wnt signaling has been attributed a crucial role in remyelination, although this issue remains controversial [55]. Furthermore, active MS plaques express Wnt signaling genes more strongly and accumulate more Wnt protein than chronic lesions and normal appearing white matter [39,56].…”
Section: Discussionmentioning
confidence: 99%